Pengembangan E-Book Berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V - Danu Kristi; Aldina Eka Andriani (Postgraduate, University of Mataram, 2023)
This research aims to develop and test the validity and effectiveness of e-books based on Problem-based Based Learning to improve science learning outcomes for class V students. The type of research used is Research and Development with the Borg and Gall research model. The subjects in this study were 26 Class V students. The data collection technique used test techniques (pretest and posttest); and non-test techniques (observation, interviews, and questionnaires). Data analysis techniques include initial data with normality and homogeneity tests; and final data analysis using the t and N-gain tests. The research results show: (1) Problem-Based Learning-based e-books were developed using the book creator application with cover components, KD, indicators, learning objectives, instructions for use, concept maps, single and mixed substance material, learning evaluation, developer biography, and bibliography ; (2) the validity test results of material experts, media experts, teachers and students are in the very appropriate category; (3) effectiveness is seen from the results of the analysis of posttest and pretest scores. The t-test results obtained a sig value. Equal to 0.000 > 0.05. The N-gain test result was 0.69 in the medium category. The conclusion from this research is that the development of an e-book based on Problem-Based Learning has been successfully developed, and is very feasible and effective for improving the science learning outcomes of class V students.